Development of An Employee Training Information System Using The Deductive Training Model - Fauziyyah, Luthfiyyah Zharifa (Penerbitan Universitas Trisakti, 2025)
The Financial Transaction Reports and Analysis Center (PPATK) provides training as a mandatory requirement to improve the competencies of its employees. However, the training registration process has not been running optimally, as it still involves multiple impractical stages and makes it difficult to monitor compliance with training requirements based on existing policies. To address this issue, this study aims to develop an employee training information system that aligns with each employee’s competencies and supports supervision of training activities across the organization to ensure compliance with established policies, thereby preventing competency and performance gaps among employees. The system development adopts a deductive training model tailored to the characteristics and needs of employees based on their respective work units. The research applies the Rapid Application Development (RAD) method, using PHP programming language with the Laravel framework and MySQL database. Data collection was carried out through observation, interviews, and literature study to understand user requirements. The SWOT analysis was conducted to evaluate the existing system. Thereafter, the newly developed system was tested using the black box method to rigorously assess its functionality. The test results indicate that all features, including training registration, duration recording, and total training hours monitoring, function as designed without errors. Based on the development and testing results, this system can be recommended as a digital, integrated, and needs-based alternative to support the management and supervision of employee training within the organization